2000
DOI: 10.1038/sj.ijo.0801225
|View full text |Cite
|
Sign up to set email alerts
|

Early macronutrient intake and overweight at five years of age

Abstract: OBJECTIVE: To examine the in¯uence of the macronutrient intake in early life on the development of overweight in children. DESIGN AND SUBJECTS: An ongoing longitudinal study including 147 randomized healthy children followed up from birth. MEASUREMENTS: Anthropometric parameters were measured at birth, 1 and 5 y of age. Dietary habits at the age of 1 and 5 were assessed by age-adjusted food-frequency questionnaires and 24 h recalls. Parents' body mass index (BMI) was also recorded. RESULTS: Parental overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
124
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 26 publications
8
124
0
8
Order By: Relevance
“…An interpretation of these associations could be that DBC increases satiety and prevents consumption of high-energydense snacks later in the morning, thus favouring energy balance, which in turn helps maintenance of normal body weight (46) . Another possible explanation of our results could be that breakfast consumption can also be a proxy of a more general healthy lifestyle (47) .…”
Section: Discussionmentioning
confidence: 99%
“…An interpretation of these associations could be that DBC increases satiety and prevents consumption of high-energydense snacks later in the morning, thus favouring energy balance, which in turn helps maintenance of normal body weight (46) . Another possible explanation of our results could be that breakfast consumption can also be a proxy of a more general healthy lifestyle (47) .…”
Section: Discussionmentioning
confidence: 99%
“…A 2006 systematic review of the dietary determinants of obesity identified several longitudinal studies that examined protein intake and obesity among children (Woodward-Lopez et al, 2006). Several of these found a positive association between protein intake and adiposity (Rolland-Cachera et al, 1995;Scaglioni et al, 2000;Skinner et al, 2004), whereas others found no association (Maffeis et al, 1998;Magarey et al, 2001;Alexy et al, 2004). The mechanisms to explain such an association, if one exists, are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…All reviews note most evidence comes from cross-sectional studies among adults, and that further rigorous inquiry is needed using valid dietary assessment methods, longer term prospective studies, and measurement and analysis of important covariates to confirm and clarify the direction and magnitude of the effects of these dietary factors and their importance in childhood. Further, of the few birth cohort studies to investigate determinants of obesity, none has measured infant feeding and early diet in sufficient detail using rigorous assessment methods to investigate associations predictive of later weight status (Scaglioni et al, 2000;Reilly et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other important factors related to physical activity and diet are known to be important determinants of childhood BMI. [27][28][29] These are also likely to influence changes in overweight status over time. We were unable to assess the effects of these exposures since information on them was not available in this study before the age of 14 y.…”
Section: Study Limitationsmentioning
confidence: 99%